1988
DOI: 10.1159/000181058
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Cryptorchidism with Human Chorionic Gonadotropin or Gonadotropin Releasing Hormone

Abstract: We have conducted a modified double-blind study on the effect of human chorionic gonadotropin (hCG), gonadotropin releasing hormone (GnRH) and placebo on bilateral and unilateral maldescended testes. One hundred and fifty-five boys with bilateral and 88 boys with unilateral cryptorchidism fulfilled the inclusion criteria and completed the treatment protocol. The boys were between 1 and 13 years of age. hCG was administered as intramuscular injections twice weekly for 3 weeks. GnRH and placebo were given intran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 10 publications
(13 reference statements)
1
24
0
Order By: Relevance
“…Job et al [29] observed that the success rate for hCG treatment was better for the bilateral inguinal testes. In this study there were no significative differences for the hCG treatment responses between the unilateral and bilateral inguinal testes; as has been observed by different authors, prescrotal testes and those that easily could be moved into a lower position had better responses [5,9,13,16,29,371. In our series, there was an evident association between the rate of success on the testicular position before treatment.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Job et al [29] observed that the success rate for hCG treatment was better for the bilateral inguinal testes. In this study there were no significative differences for the hCG treatment responses between the unilateral and bilateral inguinal testes; as has been observed by different authors, prescrotal testes and those that easily could be moved into a lower position had better responses [5,9,13,16,29,371. In our series, there was an evident association between the rate of success on the testicular position before treatment.…”
Section: Discussionsupporting
confidence: 60%
“…The use of gonadotropin releasing hormone (GnRH) was promoted by Job et al [28], who postulated that some cryptorchid patients may have a hypothalamic-hypophyseal dysfunction, a theory that has not been unanimously accepted [14]. In a double-blind study performed in 243 boys with bilateral cryptorchidism, Christiansen et al [9] found in both bilateral and unilateral cryptorchidism the rate of testicular descent was better with hCG than with GnRH.…”
Section: Discussionmentioning
confidence: 99%
“…The theoretical basis for its use is to stimulate the Leydig cells to produce testoster- one, and thereby induce testicular descent [7]. The hCG treatment has its action on all male reproductive system (testis, prostate, seminal vesicles and epididymis).…”
Section: Discussionmentioning
confidence: 99%
“…Hormonal treatment with Human Chorionic Gonadotropin (hCG) or gonadotropin releasing hormone may be initially administered for cryptorchidism because it should promote the testicular descent in about 10% -65% of cases [7]. The theoretical basis for its use is to stimulate the Leydig cells to produce testosterone, inducing inguinal-scrotal testicular descent.…”
Section: Open Accessmentioning
confidence: 99%
“…26 Bilateral cases seem to harbour the best response (25-30%). 27 There have been reports suggesting that administration of gonadotropin-releasing hormone (GnRH) either pre or postorchidopexy may improve fertility based on improved fertility indices (ascertained by proxy with the ratio of adult spermatogonia per tubule on testicular biopsies taken at the time of orchidopexy). [28][29][30] This is a highly controversial topic with conflicting recommendations having been published 28,31 and should therefore be regarded as experimental.…”
Section: Hormonal Stimulation/hormonal Therapymentioning
confidence: 99%